Peer Support Group through The Hulonthalo Emotion Card Method on Self-awareness among Adolescents - Hinelo, Annisa; Kasim, Vivien Novarina A; Antu, Mihrawaty S; Aini, Muthia Qurrota; Wardhany, Rifa Az Zahra; Ufairah, Putri Sally (Jurnal Keperawatan Profesional (KEPO), 2025)
Adolescence, as a dynamic developmental phase, was often characterized by emotional fluctuations. The Hulonthalo Emotion Card, a culturally based innovation, was selected as a medium to enhance adolescents’ self-awareness. This study aimed to identify the influence of peer support groups using the Hulonthalo Emotion Card method on self-awareness among adolescents at SMK Negeri 3 Gorontalo. This research employed a quasi-experimental design with a non-equivalent control group design. The sample consisted of 67 students, who were selected using total sampling. Data analysis was carried out using the Wilcoxon signed-rank test and the Mann-Whitney U test. The results, analyzed using the Wilcoxon test, showed a change in adolescents’ self-awareness before and after the peer support group intervention using the Hulonthalo Emotion Card method in both the experimental and control groups at SMK Negeri 3 Gorontalo. The experimental group showed a p-value of 0,000 (p-value < 0,05), while the control group showed a p-value of 0,250 (p-value > 0,05). It was concluded that the peer support group intervention using the Hulonthalo Emotion Card method had a significant influence on self-awareness among adolescents at SMK Negeri 3 Gorontalo. This study was expected to encourage adolescents to be more active in managing their emotions.